Pharmacokinetics and analgesic effectiveness of intravenous parecoxib for tonsillectomy ± adenoidectomy. Issue 12 (25th October 2016) - Tan, Lena; Taylor, Elsa; Hannam, Jacqueline A.; Salkeld, Lesley; Salman, Sam; Anderson, Brian J.
Summary: Background: Few pharmacokinetic (PK) and pharmacodynamic (PD) data exist for COX‐2 selective inhibitors in children. We wished to characterize the PKPD of parecoxib and its active metabolite, valdecoxib, in this population. Methods: Children ( n = 59) were randomized to parecoxib 0.25 mg·kg −1, 1 mg·kg −1, and 2 mg·kg −1 during tonsillectomy ± adenoidectomy. Samples (4–6 per child) were obtained from indwelling cannula over 6 h. A second group of inpatient children ( n = 15) given 1 mg·kg −1 contributed PK data from 6 to 24 h. Pain scores and rescue medication for the first group were recorded postoperatively for up to 24 h. PK data were pooled with those (10 samples/24 h) from a published study of children ( n = 38) who underwent surgery. A three‐compartment parent and one‐compartment metabolite model with first‐order elimination was used to describe data using nonlinear mixed effects models. An E MAX model described the relationship between dose and rescue morphine equivalents during recovery. Results: Parecoxib PK parameter estimates were CLPARECOXIB 19.1 L·h −1 ·70 kg −1, V1PARECOXIB 4.2 L·70 kg −1, Q2PARECOXIB 6.29 L·h −1 ·70 kg −1, V2PARECOXIB 130 L·70 kg −1, Q3PARECOXIB 6.02 L·h −1 ·70 kg −1, and V3PARECOXIB 2.03 L·70 kg −1 . We assumed all parecoxib was metabolized to valdecoxib with CLVALDECOXIB 9.53 L·h −1 ·70 kg −1 and VVALDECOXIB 51 L·70 kg −1 . There was no maturation of clearance over the age span studied. There were no differences in pain scores between groups on waking, discharge, 12 h, or 24 h. There were no differences in analgesia consumption over 24 h between groups for tramadol, fentanyl, and morphine rescue use. Fentanyl and morphine consumption, expressed as morphine equivalents (0.13 mg·kg −1 ) in the 0.25 mg·kg −1 group, was greater than that observed in the 1 or 2 mg·kg −1 groups (0.095 mg·kg −1 ) in PACU. Conclusions: Parecoxib 0.9 mg·kg −1 in a 2‐year‐old, 0.75 mg·kg −1 in a 7‐year‐old, and 0.65 mg·kg −1 in a 12‐year‐old child achieves dose equivalence of 40 mg in a standard 70 kg person. Clearance maturation may occur in infants younger than the current cohort. Parecoxib doses above 1 mg·kg −1 add no additional analgesia. Abstract :